A LITURGIA DA PALAVRA NA CELEBRAÇÃO EUCARISTICA - P. Waldomiro O. Piazza (Perspectiva Teológica, 1976)
This article shows the eucharistic celebralion as a Word in its full meaning. The Word itself lends meaning to the rite celebrated. Through it there is established a true "'dialog" between man and God. The author develops the theory looking forward to threc aspects: The Word, The Liturgy, and the eucharistic celebration. He conciude.s that the Eucharistic celebration should not be considered as a mere external act of "religion or as a mere public testimony of" faith, but, over all, as the fultillment of religious lite. because in it we effect the complete union of man to God.